Fear of knowledge : against relativism and constructivism - Boghossian, Paul Artin (Oxford, UK : Clarendon, 2006)
Relativist and constructivist conceptions of truth and knowledge have become orthodoxy in vast stretches of the academic world. This work examines such views and exposes their fundamental flaws.
Includes bibliographical references (p. 132-135) and index.
Keywords: Knowledge, Theory of; Objectivity; Constructivism (Philosophy)